Genome-Wide Analysis of Escherichia coli Isolated from Dairy Animals Identifies Virulence Factors and Genes Enriched in Multidrug-Resistant Strains - Bradd J. Haley; Seon Woo Kim; Serajus Salaheen; Ernest Hovingh; Jo Ann S. Van Kessel (MDPI AG, 2023)
The gastrointestinal tracts of dairy calves and cows are reservoirs of antimicrobial-resistant bacteria (ARB), which are present regardless of previous antimicrobial therapy. Young calves harbor a greater abundance of resistant bacteria than older cows, but the factors driving this high abundance are unknown. Here, we aimed to fully characterize the genomes of multidrug-resistant (MDR) and antimicrobial-susceptible Escherichia coli strains isolated from pre-weaned calves, post-weaned calves, dry cows, and lactating cows and to identify the accessory genes that are associated with the MDR genotype to discover genetic targets that can be exploited to mitigate antimicrobial resistance in dairy farms. Results indicated that both susceptible and resistant E. coli isolates recovered from animals on commercial dairy operations were highly diverse and encoded a large pool of virulence factors. In total, 838 transferrable antimicrobial resistance genes (ARGs) were detected, with genes conferring resistance to aminoglycosides being the most common. Multiple sequence types (STs) associated with mild to severe human gastrointestinal and extraintestinal infections were identified. A Fisher's Exact Test identified 619 genes (ARGs and non-ARGs) that were significantly enriched in MDR isolates and 147 genes that were significantly enriched in susceptible isolates. Significantly enriched genes in MDR isolates included the iron scavenging aerobactin synthesis and receptor genes (iucABCD-iutA) and the sitABCD system, as well as the P fimbriae pap genes, myo-inositol catabolism (iolABCDEG-iatA), and ascorbate transport genes (ulaABC). The results of this study demonstrate a highly diverse population of E. coli in commercial dairy operations, some of which encode virulence genes responsible for severe human infections and resistance to antibiotics of human health significance. Further, the enriched accessory genes in MDR isolates (aerobactin, sit, P fimbriae, and myo-inositol catabolism and ascorbate transport genes) represent potential targets for reducing colonization of antimicrobial-resistant bacteria in the calf gut.